2018
DOI: 10.1016/j.ejvs.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

High Density of Periaortic Adipose Tissue in Abdominal Aortic Aneurysm

Abstract: The results suggest a relation between the deposition of PVAT and AAA pathophysiology. Further research should explore the exact underlying processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 25 publications
1
55
0
Order By: Relevance
“…It was found that PVAT volume correlated well with the aortic dimension in both thoracic and abdominal regions. This data is congruent with previously publish studies investigating similar endpoints including CVD risk factors and abdominal aortic aneurysms [5][6][7].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…It was found that PVAT volume correlated well with the aortic dimension in both thoracic and abdominal regions. This data is congruent with previously publish studies investigating similar endpoints including CVD risk factors and abdominal aortic aneurysms [5][6][7].…”
supporting
confidence: 91%
“…A subset of PVAT that surrounds the coronary arteries, epicardial fat, has been well studied in the development of coronary artery disease [4]. Another subset of PVAT, periaortic adipose tissue has also been implicated in CVD, however, previous studies have limited their investigation to a specific population, unique depots, or a single CVD [5][6][7]. Herein, the current study describes the quantification of periaortic adipose tissue volume in both the thoracic and abdominal regions in a unique population and correlates this value to specific measures of CVD.…”
mentioning
confidence: 99%
“…The study by Dias-Neto et al, published in this issue, provides real world evidence that PVAT is involved in AAA pathophysiology via local mechanisms in humans. 4 The presence of an AAA was an independent predictor of higher PVAT density around the aneurysm sac compared to the healthy neck and this intra-individual PVAT difference was positively associated with aortic volume.…”
mentioning
confidence: 85%
“…The design of the studies included retrospective, prospective, and longitudinal cohort and case-control studies. All three studies matched the AAA cases and comparators for age and sex (37)(38)(39). In a multicenter retrospective case-control study, comparison of participants with asymptomatic AAA, aortoiliac occlusive disease (AIOD), and healthy controls suggested that AAA was associated with higher PVAT density and the visceral to subcutaneous adipose tissue (VAT/SAT) ratio was significantly greater in AAA patients (37).…”
Section: Studies Examining the Association Of Pvat With Aaamentioning
confidence: 99%
“…All studies reported the methods used to image the aorta, methods used for aortic diameter assessment and adjusted for potential confounders during analysis (Table 4) (37)(38)(39). Two studies reported the sample size estimate used (37,38). Only one study blinded the observer during analysis of experimental data (37).…”
Section: Quality Of Human Studies Investigating the Association Of Pvmentioning
confidence: 99%